The Historical Perspective on the Donald Trump Puzzle: A Review of Barry Eichengreen’s The Populist Temptation: Economic Grievance and Political Reaction in the Modern Era - Sonin, Konstantin (Journal of Economic Literature, 2022)
In The Populist Temptation: Economic Grievance and Political Reaction in the Modern Era, Barry Eichengreen relies on historical and contemporary evidence to analyze major episodes of populism in the twenty-first century, the Trump election in the United States, and Brexit in Europe. Populism—an anti-elite, authoritarian, and nativist movement—rises in times of economic and political discontent because elites, the winners of the preceding period, are unwilling or unable to share their winnings with the losers. This review asks for a model that would allow one to differentiate a destructive populism wave and a constructive adjustment of the political system to changing circumstances.(JEL D72, D73, N40)